ANALISIS KEPUASAN KERJA PEGAWAI DI LINGKUNGAN DINAS PERTAMBANGAN KABUPATEN KUTAI TIMUR - Marjoni Rachman Esther Tri Oktora Situmorang (ADMINISTRASI PUBLIK, 2017)
This study aims to find and describe Job Satisfaction in the Mining Service Offices of East Kutai Regency. The approach used in this research is qualitative descriptive approach. In this research will be a description of three indicators, namely Compensation, Job Placement and Work Environment.The results showed that Job Satisfaction Level of Employees in Mining Service Area of East Kutai Regency obtained a score of 71% and this is included in the category quite well. Thus the formulation of problems and hypotheses in this study have been answered and proven well.